Endoscopic features with linked-color imaging of non–Helicobacter pylori Helicobacter-associated gastritis: a case study - Tsutomu Takeda, MD, PhD; Daisuke Asaoka, MD, PhD; Shu Hirai, MD, PhD; Masahiko Nakamura, MD, PhD; Akihito Nagahara, MD, PhD (VideoGIE, 2024)
Background and Aims: The endoscopic findings of non–Helicobacter pylori Helicobacter (NHPH) are not widely known. Linked-color imaging (LCI) has emerged as a new system for image-enhanced endoscopy (IEE) that enhances color tone and improves visibility. The aim of this case study was to assess how endoscopic findings of NHPH are enhanced with LCI. Methods: We report the case of a 72-year-old woman in whom an NHPH species was found during EGD using LCI. Results: The EGD did not reveal any endoscopic findings of diffuse redness, patchy redness, or atrophy. However, erosions, nonuniform redness, and crack-like mucosa were seen in the antrum, as well as LCI-enhanced endoscopic findings. In addition, nodular gastritis and a white marbled appearance were also observed in the antrum. LCI and blue-laser imaging enhanced the endoscopic findings. Floating bacterial bodies with a fine coil-like shape and diameter longer than that of H pylori were pathologically observed in the mucus, suggesting NHPH. A polymerase chain reaction test led to a diagnosis of Helicobacter suis. Conclusions: Our case demonstrates that IEE is useful in diagnosing NHPH. The detection of NHPH using IEE enabled us to contribute to an improved diagnosis of NHPH.